Terminologiebestuur in Suid-Afrika. 'n Beoordeling van drie werkmetodes - Ferreira, Dina; du Plessis, Theodorus (Lexikos, 2007)
Abstract: Terminology Management in South Africa. A Review of Three Working Methods. The officialising of eleven languages in South Africa has resulted in the ever increasing need for the development, the elaboration and the management of terminology as well as the distribution of terminological information in all of these languages. This article reviews three terminological working methods at present successfully used in terminology planning, terminology coordination and terminology management. It was established through the research that terminology management is dealt with differently in different environments, administered by different people and results in different products. The aims with the collection and dissemination of terminology thus have a very important influence on the working method used for terminology management within a specific environment. The three working methods are known as the linguistically oriented working method, the translation oriented working method and the language planning oriented working method. The implications of the different working methods within the South African situation are evaluated to establish which one will at present provide the best option for terminology development and terminology management in South Africa.Keywords: DEVELOPED LANGUAGES, DEVELOPING LANGUAGES, INDIGENOUS LANGUAGES, LANGUAGE DEVELOPMENT, LANGUAGE PLANNING, LANGUAGE PLAN-NING ORIENTED WORKING METHOD, LINGUISTICALLY ORIENTED WORKING METHOD, MARGINALISED LANGUAGES, MULTILINGUAL COMMUNICATION, OFFICIAL LAN-GUAGES, SOURCE LANGUAGE, TARGET LANGUAGE, TERMINOLOGY, TERMINOLOGY DEVELOPMENT, TERMINOLOGY MANAGEMENT, TERMINOLOGY WORK, TRANSLATION ORIENTED WORKING METHOD, WORLD LANGUAGEOpsomming: Die verampteliking van elf tale in Suid-Afrika het tot gevolg dat daar 'n steeds groter wordende behoefte aan die ontwikkeling, die uitbouing en die bestuur van terminologie asook die verspreiding van terminologiese inligting in al hierdie tale bestaan. Hierdie artikel beoordeel drie terminologiese werkmetodes wat tans suksesvol gebruik word by terminologiebe-planning, terminologiekoördinering en terminologiebestuur.Deur die navorsing is daar vasgestel dat terminologiebestuur in verskillende omgewings verskillend aangepak word, deur verskillende persone geadministreer word en verskillende pro-dukte tot gevolg het. Die doelwitte met die versameling en disseminering van terminologie het dus 'n baie belangrike invloed op die werkmetode wat by terminologiebestuur binne 'n spesifieke omgewing gebruik word.Die drie werkmetodes staan bekend as die linguisties georiënteerde werkmetode, die verta-lingsgeoriënteerde werkmetode en die taalbeplanningsgeoriënteerde werkmetode. Die implikasies van die verskillende werkmetodes word binne die Suid-Afrikaanse situasie ondersoek om te bepaal watter een tans die beste opsie vir terminologieontwikkeling en terminologiebestuur in Suid-Afrika bied.Sleutelwoorde: AMPTELIKE TALE, BRONTAAL, DOELTAAL, GEMARGINALISEERDE TALE, INHEEMSE TALE, LINGUISTIES GEORIËNTEERDE WERKMETODE, MEERTALIGE KOMMUNIKASIE, ONTWIKKELDE TALE, ONTWIKKELENDE TALE, TAALBEPLANNING, TAALBEPLANNINGSGEORIËNTEERDE WERKMETODE, TAALONTWIKKELING, TERMINO-LOGIE, TERMINOLOGIEBESTUUR, TERMINOLOGIEONTWIKKELING, TERMINOLOGIEWERK, VERTALINGSGEORIËNTEERDE WERKMETODE, WÊRELDTAAL